Research on tourism development strategy of winery in Penglai Qiushan Valley based on SWOT-AHP model - WANG Yibing, JIANG Jiamin, LI Yueyue, ZHANG Youwen, LIU Weiping (Zhongguo niangzao, 2024)
As a product of the combination of wine industry and tourism, winery tourism can promote the integrated development of primary, secondary and tertiary industries, and is a tourism project with great development potential. Penglai district, as one of the early developing winery tourism producing areas in China, has made initial progress in winery tourism, but now it is also facing the problem of how to better integrate resources to achieve sustainable development. Based on the SWOT model, the strengths, weaknesses, opportunities as well as threats of the development of winery tourism in Penglai Qiushan Valley were analyzed, the index system of development factors was set up, the weights of each factor were calculated using analytic hierarchy process (AHP), and a strategic quadrilateral was constructed. The results showed that the strengths of Penglai Qiushan Valley winery tourism development were greater than the weaknesses, the opportunities were higher than the threats, and a strength-based strategy should be adopted. Based on the above analysis, corresponding suggestions were put forward in terms of its own strengths, location influence and characteristic tourism experience, with a view to realizing sustainable development.